Effect of Supply Chain Coordination on Performance: A Serial Mediation Model of Trust, Agility, and Collaboration - Kocoglu, Ipek; Keskin, Halit; Cemberci, Murat; Civelek, Mustafa Emre (IGI GLOBAL, 2022)
Research on supply chain management (SCM) focuses on what factors of a supply chain enable firms to achieve high performance. It examines the effect of two strategically important pillars: supply chain relationships or capabilities. However, their isolated investigation leads to a limited understanding of how they can be combined to increase firm performance. In this study, the authors argue that beyond their direct effects, the relational and the capability-based determinants of a supply chain have a network of indirect relationships that concurrently and differentially affect firm performance. Building on the relational and resource-based views, the authors develop a serial-mediation model examining the mediating effects of trust in supply chain and collaborative advantage (i.e., relational determinants) and supply chain agility and coordinated supply chain (i.e., capability-based determinants) of SCM. Through the use of hierarchical linear regression analysis, they show that trust, agility, and collaboration act as serial mediators that carry the indirect effect of coordination to firm performance.
Keywords: Collaborative Advantage; Coordinated Supply Chain; Supply Chain Agility; Supply Chain Management; Trust in Supply Chain; COMPETITIVE ADVANTAGE; MANAGEMENT; FIRM; IMPACT; INNOVATIVENESS; CAPABILITIES; ANTECEDENTS; KNOWLEDGE; VIEW; Business & Economics